Adsorption of Cr(VI) Using Organoclay/Alginate Hydrogel Beads and Their Application to Tannery Effluent - Mayra X. Muñoz-Martinez; Iván F. Macías-Quiroga; Nancy R. Sanabria-González (Gels)
The tanning industry is among the most environmentally harmful activities globally due to the pollution of lakes and rivers from its effluents. Hexavalent chromium, a metal in tannery effluents, has adverse effects on human health and ecosystems, requiring the development of removal techniques. This study assessed the efficacy of organobentonite/alginate hydrogel beads in removing Cr(VI) from a fixed-bed adsorption column system. The synthesized organobentonite (OBent) was encapsulated in alginate, utilizing calcium chloride as a crosslinking agent to generate hydrogel beads. The effects of the volumetric flow rate, bed height, and initial Cr(VI) concentration on a synthetic sample were analyzed in the experiments in fixed-bed columns. The fractal-like modified Thomas model showed a good fit to the experimental data for the asymmetric breakthrough curves, confirmed by the high R2 correlation coefficients and low χ2 values. The application of organoclay/alginate hydrogel beads was confirmed with a wastewater sample from an artisanal tannery industry in Belén (Nariño, Colombia), in which a Cr(VI) removal greater than 99.81% was achieved. Organobentonite/alginate hydrogels offer the additional advantage of being composed of a biodegradable polymer (sodium alginate) and a natural material (bentonite-type clay), resulting in promising adsorbents for the removal of Cr(VI) from aqueous solutions in both synthetic and real water samples.